METAMORFOIS OF MISSIONARY CHURCH SERVICES IN THE DIGITAL ERA - Kristian Pebrianto; Lenny Indriany Noya; Purba, Margaretha (Jurnal Matetes STT Ebenhaezer, 2023)
In the digital era, namely 4.0 and starting to enter 5.0, is an era where all things can be accessed and can even be done through technology. The rapid development of technology today, brings positive and negative things. The church itself must essentially be a missionary church. The presence of the church is a representation of God on earth. Therefore, the church will continue to adapt to various developments accompanied by technological advances. However, with increasingly sophisticated technological advances in this digitalization era, many churches have begun to discard and replace true theological traditions. Not only that, currently various forms of church activities are also experiencing changes, for example online worship, missionary services that can be reached at this time can only be through the internet. therefore, the purpose of this writing is that as a missionary church it cannot limit itself or even cover itself with the changes that occur which are influenced by current technological advances. The method that the writer uses is qualitative-descriptive by using related literatures.